The catalytic effect of the Au(111) and Pt(111) surfaces to the sodium borohydride hydrolysis reaction mechanism: A DFT study. (2nd August 2018) - Genç, A.E.; Akça, A.; Kutlu, B.
Abstract: In this research, hydrolysis mechanism of sodium borohydride (NaBH4 ) have been studied theoretically on Au (111) and Pt (111) noble metal surfaces by periodic density functional theory calculations. Elementary reaction steps have been generated based on study of borohydride oxidation. Reaction intermediates which have plethora of hydroxyl (OH) radical(s) have been produced by decomposition of water molecule(s). In order to investigate surface effect, we have followed two different routes. The first route is that the atomic and molecular structures in the reaction steps have been optimized in 3-d box without a catalyst. At second one, they were interacted with the Au (111) and Pt (111) surfaces to compare relative behavior with reference to the non-catalytic medium. The relative energy diagrams were produced by relative energy differences which is useful to generate energy landscape using required/released energies in order to pursue the reaction. Three main peaks that means considerable energy changes have been observed to proceed the reaction in the non-catalytic medium. Then, changes in the energy differences depending on surfaces have been discussed. Although acquired relative energies are not within chemical accuracy, they are very successful to show the affect of the OH radical concentration to the potential energy diagram. Pt (111) surface have been found more reactive than Au (111) surface for Sodium Borohydride Hydrolysis reaction, as it is obviously coherent with the literature. Graphical abstract: Image 1 Highlights: Relative energy definition is very usable to differ catalytic activity. The co-existence of Na and B considerably changes the adsorption mechanism. Barrier of the reaction increases with the increasing with the OH molecules. OH co-adsorption with NaB complexes makes the reaction more facile. Flatness of the relative energy diagram is a sign of relative activity.